Effects of pirfenidone on experimental head injury in rats - GÜVENÇ, YAHYA (My University, 2022)
Traumatic brain injury (TBI) continues to be a significant public healthcare concern. Neuroinflammation that occurs in the secondary phase of TBI leads to cognitive and physical dysfunction. A number of therapeutic modalities have been evaluated in an attempt to find a suitable treatment. The only drug approved for the treatment of idiopathic pulmonary fibrosis, pirfenidone, has been evaluated for its antifibrotic, anti-inflammatory, and anti-oxidant properties for various disorders, but this is the first study to examine its effects in an experimental TBI model. Twenty-four Wistar rats were randomly divided into three groups: control, trauma, and pirfenidone. The two latter groups underwent experimental diffuse cortical injury mimicking TBI. Neurological assessment was performed using the Garcia test, histological analysis was performed to examine neuroprotective and anti-inflammatory effects, and biochemical analyses of neuron-specific enolase (NSE), S-100B, caspase-3, and thiobarbituric acid reactive substances were performed. The pirfenidone group had a better Garcia test score (P=0.001), an increased anti-inflammatory effect (P<0.001), and an enhanced neuroprotective effect (P=0.007) along with decreased NSE, S100B, and TBARS levels compared to the trauma group. However, pirfenidone did not show a beneficial effect on caspase-3 levels. Pirfenidone may help decrease mortality and morbidity rates after TBI through its anti-inflammatory and antioxidant effects.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Biochemistry; Internal Medicine Sciences; Internal Diseases; Oncology; Surgery Medicine Sciences; Pathology; Life Sciences; Natural Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); PATOLOJİ; Biyoloji ve Biyokimya; Yaşam Bilimleri (LIFE); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PATHOLOGY; BIOLOGY & BIOCHEMISTRY; Life Sciences (LIFE); Histology; Pathology and Forensic Medicine; Biochemistry (medical); Pirfenidone; traumatic brain injury; neuroprotective; anti-inflammatory; anti-oxidant; NEURON-SPECIFIC ENOLASE; PROTEIN